TRENDS AND PATTERN OF SUGAR INDUSTRY IN HARYANA: A RETROSPECT - Savita Nahar (International Journal of Innovations in Engineering Research and Technology, 2015)
Haryana, the land of agriculture and culture, appeared on the political map of India being a separate State on 1st November, 1966 as a result of reorganization of Punjab State. At that point of time there were only 7 districts in the State namely Ambala, Karnal, Rohtak, Gurgaon, Mohendragarh, Hisar and Jind. According to the Economic Survey (2010-11)5, ‘By now, for administrative reasons the whole State has been divided into four divisions (Ambala, Hisar, Rohtak and Gurgaon), 54 sub-divisions, 21 districts, 74 tehsils, 44 sub-tehsils, 119 development blocks, 106 towns and 6955 inhabited villages. Haryana is spread over an area of 44,212 square kilometers with a population of 210,82,989 as on 31st March, 2001’. Haryana is located in the northwest part of the country and the climate is arid to semi-arid with average rainfall of 455 mm. Around 70 percent rainfall is received during the month from July to September and the remaining rainfall is received during Dec. to Feb. The National Capital Territory of Delhi juts into Haryana. The State is bounded by Uttar Pradesh and Delhi in the East, Punjab in the West, Himachal Pradesh in the North and Rajasthan in the South.